El conflicto de Guyana - Alcan y la nacionalización de Demba - Girvan, Norman (Estudios Internacionales, 1972)
Guyana's Prime Minister Forbes Burnham announced his government's decision to nationalize the Demerara Bauxite Company (DEMBA), the leading foreign exchange and tax revenue generating company in Guyana, owned by Alcan Aluminum Limited. This decision implied a fundamental change in the organization of the Guyana economy and constituted the first concrete deviation, on the part of a Caribbean Commonwealth government, from the policy of accommodation to external capital. This is a preliminary analysis of the economic policy that determined the relations between ALCAN and Guyana from the beginning of the same, more than fifty years ago. This paper attempts to expose the logic of the events that led to the nationalization of DEMBA, in the context of the structural relationship between the economic needs of a multinational company and the economic policy of a Caribbean country.